Promotion of Education in Geosciences and UNESCO Global Geoparks - Fernandes, Magda (2018)
Considering that Earth is an active planet and that anthropic action contributes to alter the planet's dynamic equilibrium, through the increase of the natural hazards and depletion or destruction of the geological heritage, often for lack of knowledge of its scientific and didactic value, the dissemination of the work developed in Geosciences as well as Education, is of the utmost importance. In this context, the dissemination and teaching of Geosciences gained another dynamic with the creation of Geoparks because, these geographically well-defined territories that possess a remarkable geological heritage, in association with the other elements of the natural and cultural heritage, have as fundamental pillars Geoconservation, Tourism and Education for Sustainability. In this context, the UNESCO Global Geoparks promote the development of educational programs and interpretive resources, contributing to the dissemination of scientific knowledge enabling a greater visibility to Geosciences among the educational community and the general public. The Estrela Aspiring Geopark, which has an area of approximately 2216 km2 and includes 9 municipalities around Estrela, is a territory where sustainable development is sought in an integrated way, based on its geological and geomorphological heritage, of national and international relevance, its biodiversity and its culture, a reflection of the secular adaptation of its communities to this mountain territory. Here we can find important marks of the last glaciation that occurred about 30,000 years ago. This aspiring UNESCO Global Geopark is promoting multidisciplinary educational programs, which include indoor and outdoor activities, aimed at different levels of education (Basic, Secondary and Higher Education), in order to foster direct contact with the geological heritage, thus contributing to the recognition of its importance and consequently to the need for its conservation, since it is only possible to value and preserve what is truly known. The Estrela Aspiring Geopark has also interpretive routes in the field of non-formal education, aimed at the general public, and thus contributing to the dissemination and preservation of the valuable natural and cultural heritage of Estrela, as well as its use in a sustainable way. This article intends to demonstrate the importance of education in the dissemination of scientific knowledge, especially in the field of Geosciences, and to reveal how UNESCO Global Geoparks can be living laboratories, where multiple didactic and learning experiences are developed.